Operative volume of newborn surgery in German University Hospitals: high volume versus low volume centers - Lacher, Martin; Barthlen, Winfried; Eckoldt, Felicitas; Fitze, Guido; Fuchs, Jörg; Hosie, Stuart; Kaiser, Martin M.; Meyer, Thomas; Muensterer, Oliver; Reinshagen, Konrad; Rothe, Karin; Seitz, Guido; et al. (European journal of pediatric surgery, 2022)
newborn surgery - pediatric surgery - Germany - centralization